Strategi krativitas agar anak semakin semangat belajar bahasa Inggris - Qurrota A'yun, Salma Nabila (Maliki Interdisciplinary Journal, 2024)
Mastery of the united kingdom language in this era of globalization is very important. However, motivating children to learn united kingdom can be a challenge. This article discusses creative strategies that can be applied to increase children’s enthusiasem for learning united kingdom. By utilizing various innovative approaches and techniques, it is hoped that children can be more enthusiastic and effective in the united kingdom learning process. This discussion is supported by various relevant and trusted academic journals from campuses in indonesia